Analysis of Genome DNA Methylation at Inherited Coat Color Dilutions of Rex Rabbits - Chen, Yang; Hu, Shuaishuai; Liu, Ming; Zhao, Bohao; Yang, Naisu; Li, Jiali; Chen, Qiuran; Zhou, Juan; Bao, Guolian; Wu, Xinsheng (Frontiers in Genetics, 2021)
Background: Dilution of color in rabbits is associated with many different genetic mechanisms that form different color groups. A number of previous studies have revealed potential regulatory mechanisms by which epigenetics regulate pigmentation. However, the genome-wide DNA methylation involved in animal coat-color dilution remains unknown. Results: we compared genome-wide DNA methylation profiles in Rex rabbit hair follicles in a Chinchilla group (Ch) and a diluted Chinchilla group (DCh) through whole-genome bisulfite sequencing (WGBS). Approximately 3.5% of the cytosine sites were methylated in both groups, of which the CG methylation type was in greatest abundance. In total, we identified 126,405 differentially methylated regions (DMRs) between the two groups, corresponding to 11,459 DMR-associated genes (DMGs). Gene ontogeny (GO) and KEGG pathway analysis revealed that these DMGs were principally involved in developmental pigmentation and Wnt signaling pathways. In addition, 2 DMRs were randomly selected to verify that the WGBS data were reliable using Bisulfite Sequencing PCR (BSP), and 7 DMGs were analyzed to establish the relationship between the level of DNA methylation and mRNA expression using qRT-PCR. Due to limitation of the small sample size, replication of the results with a larger sample size would be important in future studies. Conclusion: These findings provide evidence that there is an association between inherited color dilution and DNA methylation alterations in hair follicles, greatly contributing to our understanding of the epigenetic regulation of rabbit pigmentation.